The Role of Quantitative C-Reactive Protein, White Blood Cell Count and Pyuria in Predicting Urinary Tract Infection among Febrile Infants and Children - Rimal, Hem Sagar; Walavalkar, Shripad J (Birat Journal of Health Sciences, 2018)
Introduction: Urinary tract infection (UTI) is among the commonest bacterial infections in infants and children that warrants early detection and management to prevent long term consequences in kidney causing significant morbidity. The prevalence of UTI varies according to age, gender, race, circumcision status of children but it occurs in 1% of boys and 1 to 3% of girls. There have been studies that have highlighted the importance of C-reactive as an inflammatory marker involved during urinary tract infection in children.Objectives: To find out how Quantitative C-reactive protein level, white blood cell count and pus cells in urine are associated in febrile infants and children with UTI. To find out the antibiotic sensitivity pattern of UTI.Methodology: A prospective cross sectional study was conducted to evaluate febrile infants and children of 2 months to 13 years of age with suspected UTI for a period of six months. Venous blood samples were sent for Quantitative estimation of CRP, White blood cell count and urine samples were sent for urine microscopy and culture sensitivity. Statistical analysis of data was done using SPSS software version 16.Results: Among 210 infants and children enrolled in the study, 62 (29.55%) had positive urine culture, representing 31.2% and 28.6% of female and male populations respectively. The sensitivity, specificity, positive predictive value(PPV) and negative predictive(NPV) value of CRP (with cut off of 1mg/dl) was 77%,81%, 63% & 90% respectively and that of WBC Count (with cut off of > 12000/ml ) were 56%, 88%, 66% & 83% respectively. Similarly for pyuria (with cut off of >10/HPF) using urine culture as gold standard were 63%, 91%,74% and 85% respectively. The most common organism found in urine culture was E. coli 49(79%). Highest number of isolates were sensitive to Nitrofurantoin(96%) and Amikacin(94%) whereas Amoxycillin was resistant to all the organism tested that was the resistance of 100%.The next common antibiotics found to be resistant was cotrimoxazole (70%).Conclusion: Quantitative C- reactive protein and White blood cell count in blood are very useful markers to predict UTI in febrile infants and children. E coli is the commonest pathogen to cause UTI and Pyuria(pus cells > 10/HPF) has high predictive value for UTI. Birat Journal of Health SciencesVol.2/No.3/Issue 4/Sep- Dec 2017, Page: 296 - 299